Prevalence of uncontrolled hypertension and contributing factors in Ethiopia: a systematic review and meta-analysis - Gobezie, Mengistie Yirsaw; Hassen, Minimize; Tesfaye, Nuhamin Alemayehu; Solomon, Tewodros; Demessie, Mulat Belete; Fentie Wendie, Teklehaimanot; Tadesse, Getachew; Kassa, Tesfaye Dessale; Berhe, Fentaw Tadese (Frontiers in Cardiovascular Medicine, 2024)
Background Uncontrolled hypertension (HTN) is a major risk factor for cardiovascular and cerebrovascular disease. The prevalence of HTN in the Ethiopian adult population is almost 20%.This study aimed to determine the prevalence of uncontrolled HTN and its contributing factors among patients with HTN in Ethiopia undergoing treatment. Methods Electronic bibliographic databases such as PubMed, Google Scholar, Hinari (Research4Life), Embase, and Scopus were searched for original records in the English language that assessed HTN control in Ethiopia and were available before 29 June 2023. The data were extracted using a format prepared in Microsoft Excel and exported to the software STATA 17.0 for analysis. The study protocol was registered at PROSPERO with the reference number CRD42023440121. Results A total of 26 studies with 9,046 patients with HTN were included in the systematic review and meta-analysis, of which 11 studies were used to assess factors contributing to uncontrolled blood pressure (BP) in patients in Ethiopia. The estimated prevalence of uncontrolled HTN in the population of Ethiopia is 51% [95% confidence interval (CI), 42%–60%]. The subgroup analysis, based on the assessment tools, region, and follow-up period, revealed that the prevalence of uncontrolled BP was highest following the guidelines of the American Heart Association/American College of Cardiology (AHA/ACC) (89%; 95% CI: 87%–91%) and in Addis Ababa (58%; 95% CI: 40%–76%), and the lowest proportion of uncontrolled BP was in the 3-month follow-up period (34%; 95% CI: 29%–39%). The presence of diabetes mellitus showed the highest impact (pooled odds ratio: 5.19; CI: 1.41–19.11) for uncontrolled HTN. The univariate meta-regression method confirmed that the sample size, year of publication, and subgroups were not sources of heterogeneity in the pooled estimates. Egger's regression test did not indicate the presence of publication bias. Conclusion More than half of the hypertensive patients in Ethiopia have uncontrolled BP. Diabetes mellitus, advanced age, male sex, and the presence of comorbidities are among the factors contributing to uncontrolled HTN in Ethiopia. The concerned bodies working in this area should implement interventional strategies and recommendations that might be helpful in achieving optimal BP in hypertensive patients. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023440121, PROSPERO (CRD42023440121).